Artemisia pallens Wall. ex. DC: A comprehensive review - Naraganahalli Dasappa Yogendra; Rajesh Ravi Kumara; Thankaswamy Arul Prakash; Rudra Prakash Mohanty; Swathi Singh; Kaniya Monappagowda Prakhyath; Paddambail Ellianna Keerthi; Krishnamoorthy Devanathan; VPPalayam Shanmugam Pragadheesh; Velusamy Sundaresan; Ram Swaroop Verma (Shahrekord University of Medical Sciences, 2024)
Davana (Artemisia pallens Wall. ex DC) is a well-known and precious essential oil-bearing plant under the family Compositae (Asteraceae). It is an erectly grown herbaceous plant exclusively cultivated as a short-term crop in south India during winter. It is distributed in the northern hemisphere in subtropical Africa, South Africa, West America, and South America; however, it is indigenous to southern India. The yearly productivity of davana oil typically falls between 8 to 10 tones. Davana oil is mainly used to flavor pastries, cakes, tobacco, and some beverages. It consists of diverse phyto-molecules and is an important and unique commodity in the fragrance, flavor, and liquor industries. It has excellent biological potential and contains volatile and nonvolatile constituents such as terpenoids, flavonoids, and alkaloids, which have high pharmacological values. Several investigations have focused on validating the importance of chemical constituents and the biological efficacy of essential oils and various extracts in multiple industries. The review focuses on the complete agronomic practices, botany, breeding, biotechnology, and chemistry of davana essential oil (DEO), viz, volatile and nonvolatile constituents, phytomedicinal and pharmacological properties, which may help researchers achieve their future goals for approaching its industrial or commercial viability as a natural product ingredient.